Divine Objectives and Decentralized Power: Islamic Thought, Postmodernism, and the Future of Global Ethics - Ahmad, Dr. Sajjad; Muhammad Hassan Abbas; Muhammad Asim Imam (South Asian Journal of Religion and Philosophy (SAJRP), 2025)
This article examines the underexplored intersections between postmodernism and Islamic thought, arguing that Maqasid al-Shariah (objectives of Islamic law) offers a robust ethical framework to address postmodernism’s normative gaps in confronting global challenges. While postmodern critiques deconstruct power hierarchies in technology, justice, and sustainability, exposing algorithmic bias, systemic oppression, and ecological exploitation, their relativistic foundations often lack actionable solutions. Conversely, Islamic thought, grounded in divine revelation, provides prescriptive principles such as Adl (justice), Mizan (balance), and Khilafah (stewardship). Through comparative analysis and case studies including Malaysia’s Shariah-compliant AI governance, Islamic Relief’s refugee programs, and Indonesia’s ecological fatwas this study demonstrates how these paradigms synergize postmodern pluralism and revitalize Islamic Ijtihad (independent reasoning), while Maqasid al-Shariah stabilizes postmodern ethics with universal norms. The findings suggest a post-secular interdisciplinary dialogue, proposing policy models that integrate Maqasid principles into global governance frameworks like the Sustainable Development Goals (SDGs). By bridging critical theory and theological ethics, this work redefines global problem-solving, balancing moral clarity with inclusive pluralism.